ОБРАЗОВАНИЕ ПАССИВНОГО ЗАЛОГА В АНГЛИЙСКОМ И В КАРАКАЛПАКСКОМ ЯЗЫКАХ - Пренова, Г. (SCIENCE and SOCIETY, 2016)
The article deals with the study of semantic peculiarities of constructions in the Active of Passive voice. There have been studied the means forming these constructions, the issues of their translation into Karakalpak and the category of voice in English and Karakalpak.
Keywords: semantics; categories of the verb; active and passive forms of the verb; voice; analytical; synthetical; transitive verb; translation